(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2023)
In this paper we give some new results for controlled g-frames and controlled dual g-frames in Hilbert C^*-modules. First, we talk about controlled g-frame characterisation and find certain conditions that are equal to them. Then, we explain the purpose controlled dual g-frames and controlled dual g-frames operator and discuss some of their characteristics.